High net power output analysis with changes in exhaust temperature in a thermoelectric generator system. (15th June 2017) - He, Wei; Wang, Shixue; Yue, Like
Highlights: The study focused on maximizing net power with changes in exhaust temperature. High exhaust temperature requires long length and narrow width. A high exhaust temperature leads to small optimal TEG module area. The same optimal exchanger height existed for different exhaust temperatures. Optimal exhaust exchanger scale design for unsteady temperature is introduced. Abstract: Several automotive manufacturers are exploring thermoelectric power generators to convert some of the waste heat from exhaust gas into useful electric power. Thus, the analysis and modeling of an effective thermoelectric generator (TEG) system is important given its applications in waste heat recovery systems. This study focuses on the applications of a TEG system in automotive exhaust heat recovery and considers the effect of changes in the exhaust temperature on exhaust exchanger scale optimization by evaluating the maximal net power output of an optimal object with a sandwich-plate tape exhaust exchanger. The study involved numerical calculation using Fortran and provided new findings with respect to the optimal performance. The results indicated that different exhaust temperatures led to significantly different heat transfer and flow resistance characteristics, and thereby led to corresponding differences with respect to the optimal design of exchanger scales. The findings indicated that different exhaust temperatures had the same optimal height. However, increases in exhaust temperature led to increases in the optimal length and reductions in the optimal width. A design method involving selection of the average values of the optimal length and width for different exhaust temperatures was developed to achieve a high net power output. A design involving an optimal height in the range of 0.004 m to 0.01 m was recommended and acceptable with corresponding optimal length and width scales given exhaust temperature changes in the range of 300–600 °C. The research shows that a high-efficiency TEG system achieved by optimizing the design of exhaust heat exchanger dimensions responded to the changes in the exhaust temperature.